Economic analysis of Lixisenatide in Diabetes Mellitus Type 2 - A. S. Kolbin; A. A. Mosikyan; A. A. Kurylev; Yu. E. Balykina; M. A. Proskurin; W. Zhao (Izdatelstvo OKI, 2018)
Usage of glucagon like peptide-1 receptors' agonists (aGLP-1) is a new step in the treatment of Diabetes Mellitus Type 2 (DM 2). General attractive effects are positive effect on bodyweight, lower risk of hypoglycemia, compliance and possibility of combination with insulin or it's analogues etc. Clinical-economic analysis of Lixisenatide in combination with insulin glargine has been performed for evaluation of reasons for state or insurance budgeting. Methods: Model of DM 2 has been used for comparison of Direct Costs (DC) of glargine+lixisenatid and basal bolus glargine+glulisine, detemir+aspart, glargine+aspart, glargine+lispro, detemir+lispro, detemir+glulisis as well as with combnations of metformin with exenatide or liraglutide. Efficacy criteria were amount of patient-years without complications during one-year period and amount of patient-years with targeted HbA1c level. Calculation cost has included: expenditures on pharmacotherapy of DM2 and complications, costs of out-patients aid, emergency and hospital treatment. Cost-efficacy ratio and incremental cost-efficacy rate as well Budget Impact have been performed. Results: Highest DC based on 2-year horizon of modelling were calculated for detemir+aspart -277 356 RUR, DC for glargine+lixisenatide was less on 5,6%. Costs of aGLP-1 and insulins were different, and expenditures on hypoglycemia too. Thus detemir+aspart were most expensive 77 763 RUR. Also in this group treatment of hypoglycemia was very costly. CERs (cost- effectiveness ratios) were 2 456 RUR, 3 752 RUR and 3 980 RUR. for glargine+glulisine, glargine+lixisenatide and detemir+aspart accordingly. Highest level of DC has been done for detemir+glulisine 281 628 RUR and detemir+lispro 278 744 RUR. Lixisenatide has led to insulin (glargine) dose reduction in compare with other combinations that reflected in less cost (54 186 RUR for glargine vs 81 289 RUR for detemir+glulisine during 2 years). Amount of patient-years with targeted level of HbA1c was the same in different treatment options but scheme glargine+lixisenatide was less costly DC among schemes with another aGLP-1 was less in glargine+lixisenatide on 65% in compare with metformin+liraglutide (741 531 RUR with 2-years of modelling horizon). Conclusion: Scheme glargine+lixisenatide more cost-saving regimen in compare with metformin+exenatide, metformin+liraglutide, detemir+short acting insulin analogues Scheme glargine+lixisenatide has not benefits in compare with glargine+glulisin but has less hypoglycemia level. Glargine+lixisenatide is an economic appropriate scheme for state (insurance) budgeting.